2009
DOI: 10.1093/annonc/mdp032
|View full text |Cite
|
Sign up to set email alerts
|

Stratified phase II trial of cetuximab in patients with recurrent high-grade glioma

Abstract: Cetuximab was well tolerated but had limited activity in this patient population with progressive HGG. A minority of patients may derive a more durable benefit but were not prospectively identified by EGFR gene copy number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(145 citation statements)
references
References 49 publications
2
137
0
3
Order By: Relevance
“…6,7 On the other hand, it was demonstrated that the anti-EGFR mAb cetuximab is effective both in vitro and in vivo using human GBM cell lines; 8 however, the use of cetuximab in GBM patients has been limited partly because of severe toxicities (grade 3 or 4 acne-like rash, hypersensitivity and serious adverse effect, 9 and its limited activity as single agent in patients with progressive high-grade gliomas in a stratified phase II trial. 10 In general, EGFR-targeted agents with a high toxicity profile may be not suitable as an add-on therapy to the standard of care in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 On the other hand, it was demonstrated that the anti-EGFR mAb cetuximab is effective both in vitro and in vivo using human GBM cell lines; 8 however, the use of cetuximab in GBM patients has been limited partly because of severe toxicities (grade 3 or 4 acne-like rash, hypersensitivity and serious adverse effect, 9 and its limited activity as single agent in patients with progressive high-grade gliomas in a stratified phase II trial. 10 In general, EGFR-targeted agents with a high toxicity profile may be not suitable as an add-on therapy to the standard of care in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several small-molecule EGFR-inhibitors such as gefitinib and erlotinib have been used in clinical trials but progression-free survival was not prolonged (van den Bent, et al, 2009). The inability to increase survival of GBM patients was also observed with lapatanib (EGFR/HER-2 inhibitor) (Neyns, et al, 2009;Thiessen, et al, 2009), and with the cetuximab, the monoclonal antibody against EGFR (Neyns, et al, 2009). The unsuccess of EGFR inhibitors in GBM treatment seems to be associated to the inactivation of PTEN and to the activation of the PI3K/Akt.…”
Section: Signaling Pathways Altered In Gbmmentioning
confidence: 99%
“…However, the maximum tolerated dose of gefitinib could be 500 to 1000 mg/kg depending on the concomitant use of non-EIAEDs or EIAEDs respectively [33]. Cetuximab, an EGFR antagonist showed limited toxicity and activity against recurrent GBM independently of the EGFR status of the tumors [34]. Overall, studies on EGFR inhibitors found no significant activity of these agents in high-grade gliomas [35].…”
Section: Molecular Targeted Therapiesmentioning
confidence: 99%